2014
DOI: 10.1155/2014/140867
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profiling of thePlasmodium falciparumPopulation Using Antigenic Molecular Markers

Abstract: About 50% of malaria infections in India are attributed to Plasmodium falciparum but relatively little is known about the genetic structure of the parasite populations. The molecular genotyping of the parasite populations by merozoite surface protein (msp1 and msp2) and glutamate-rich protein (glurp) genes identifies the existing parasite population in the regions which help in understanding the molecular mechanisms involved in the parasite's drive for survival. This study reveals the genetic profile of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
(23 reference statements)
3
7
0
Order By: Relevance
“…In southeast Asia, MOI of P. falciparum for hypoendemic regions ranges from 1.00 to 2.70. 9,16,17 A high level of heterozygosity (0.80-0.93) for all the three markers in Bangladesh was recorded in this study. This finding is higher than the heterozygosity range (0.51-0.65) reported earlier in the southeast Asia/Pacific region but quite comparable to some malaria-hyperendemic African countries (0.76-0.98).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…In southeast Asia, MOI of P. falciparum for hypoendemic regions ranges from 1.00 to 2.70. 9,16,17 A high level of heterozygosity (0.80-0.93) for all the three markers in Bangladesh was recorded in this study. This finding is higher than the heterozygosity range (0.51-0.65) reported earlier in the southeast Asia/Pacific region but quite comparable to some malaria-hyperendemic African countries (0.76-0.98).…”
Section: Discussionsupporting
confidence: 51%
“…Usually, the prevalence of polyclonal infections ranges from 20% to 30% for areas with hypoendemicity, 50% in hypo/mesoendemic areas to almost 100% in some holoendemic areas. 25 A positive association between MOI and endemicity of P. falciparum has been reported in several studies, 8,9,11,12,17,23 although some exceptions where high MOI was observed in hypoendemic areas are known. 14,19 In the present study, MOI was 1.51, 1.25, and 1.08 for msp1, msp2, and glurp, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The P. falciparum merozoite surface proteins 1 and 2 ( msp - 1 and msp - 2) and glutamate-rich protein ( glurp) genes are significant molecular markers, highly effective in differentiating monoclonal from multiclonal infections within infecting parasite strains, including their utilization in discriminating recrudescence from re-infecting alleles [ 9 , 10 ]. They are also parasite proteins under consideration as potential vaccine candidates, either individually or in combination with other parasite proteins, because of their preponderance at various stages of the parasite life cycle [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%